Cellular strategies for retinal repair by photoreceptor replacement. (May 2015) - Jayakody, Sujatha A.; Gonzalez-Cordero, Anai; Ali, Robin R.; Pearson, Rachael A.
Abstract: Loss of photoreceptors due to retinal degeneration is a major cause of blindness in the developed world. While no effective treatment is currently available, cell replacement therapy, using pluripotent stem cell-derived photoreceptor precursor cells, may be a feasible future treatment. Recent reports have demonstrated rescue of visual function following the transplantation of immature photoreceptors and we have seen major advances in our ability to generate transplantation-competent donor cells from stem cell sources. Moreover, we are beginning to realise the possibilities of using endogenous populations of cells from within the retina itself to mediate retinal repair. Here, we present a review of our current understanding of endogenous repair mechanisms together with recent progress in the use of both ocular and pluripotent stem cells for the treatment of photoreceptor loss. We consider how our understanding of retinal development has underpinned many of the recent major advances in translation and moved us closer to the goal of restoring vision by cellular means.